Perbedaan Harapan Pelanggan Persepsi Dimensi Kualitas Layanan di Pecel Solo Restaurant - Erwan Nurhidayat (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2019)
Increasing competition especially in the culinary business , make Pecel Solo Restaurant should strive to meet the expectations of customer with the needs and desires of customer so that what is accepted by consumers as expected earlier. The purpose of this study was to determine if there are any the difference (gap) between the expectation with the customers perception of service quality dimensions on Pecel Solo Restaurant. The sampling technique using non probability sampling technique with the sample size is 68 respondents. Data analysis methods used are Mann Whitney , and the Importance Performance Analysis